PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE (GCG) TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN YANG LISTING DI BEI - Alfinur, Alfinur (Jurnal Ekonomi Modernisasi, 2016)
The purpose of this study was to determine the effect of managerial ownership, institutional ownership and independent directors to corporate value. The population in this study amounted to 383 companies. Sampling in this study using purposive sampling and obtained 66 samples. This study tested using regression analysis techniques. The results of this study indicate that (1) Managerial ownership negative effect on the value of the company. (2) Institutional ownership has no effect on the value of the company. (3) Independent commissioner has positive effect on firm value